Avaliação dos efeitos de protocolos de manuseio mínimo em parâmetros fisiológicos de recém-nascidos pré-termo com doença de membrana hialina em ventilação mecânica - Laura Alves Cabral (2011)
The literature recommends the practice of minimal handling during the first 72 hours of life to preterm newborn due to the risk of periventricular and intraventricular hemorrhage (PIVH) in the first days of life. However, there are few published studies that evaluate the effects of the use of minimal handling protocol in the group of preterm infants and the period needed to ensure greater physiological stability. The aim of this study was to evaluate and compare the effects of minimal handling protocols on physiological parameters during the first three days of life in preterm infants with hyaline membrane disease on mechanical ventilation (MV) after surfactant replacement therapy. It was conducted a prospective observational clinical trial through continuous monitoring of variables of oxygen saturation (SpO2), heart rate (HR) and axillary temperature (AT) and counting the number and type of procedure held in two groups of preterm infants. Furthermore, adverse events associated with the variables were analysed. In the first group the babies remained in supine with the head in midline and raised to 30°. No exchange of sheets mattress was done within 12 hours of life. The second group remained 72 hours in these conditions during the first 72 hours of life. Cranial ultrasound exam was done at the end of the third day of life. The descriptive analysis was performed to identify the main characteristics of patients and adverse events. The analysis between categorical variables and the protocols which infants underwent was performed using the Fisher Exact Test. To analyze continuous quantitative variables it was used the nonparametric test Mann-Whitney. This test was used to assess the distribution and comparison between groups regarding adverse events, number and type of procedures. It was used the significance level of 5%. In addition, fidelity analysis was performed to verify effectiveness of the use of handlings protocols in the study. The analysis of the occurrence of adverse events showed that those related to HR had more occurrences followed by events related to AT and finally those related to SpO2. All events studied showed great variability around the mean. These findings may be explained by immaturity of the autonomic system of the preterm infants and by the type of management. The comparison of the protocols showed no significant difference in analyzed adverse events. However, it was observed that there is a significant difference between the two groups related to PIVH. Only the babies submitted to the protocol of 12 hours presented this finding in the cranial ultrasound exam. These results suggest that duration and conditions in minimum handling do not have significant effects on physiological parameters in preterm infants with hyaline membrane disease on MV. However, these factors may influence the development of PIVH on these babies during the first 72 hours of life. The fidelity analysis showed that the methods used in this study assured, in most cases, effectiveness in the use of protocols for minimum handling in the neonatal intensive care unit.